The Technological Profile of a Language Teacher in Mexico: A Revision of Standards - Borromeo García, César Augusto (2015)
Standardization is a process that has been increasing in the past years because of globalization. English Language Teaching is ruled by standardization and uniformization of processes and knowledge. It is possible to find topics related to Information and Communication Technologies (ICT) among these knowledge and processes. Nevertheless, measuring different contexts with different conditions with the same considerations is a process that many consider incorrect. In this paper, a selection of international standards regarding ICT in English Language Teaching is proposed. First, background of the Mexican context is presented. Next, the process of comparison and the description of the selected literature is shown. Finally, a suggestion of adequate standards for the Mexican context is presented.